Post-PCI acute heart failure is an independent predictor of long-term mortality in patients with chronic kidney disease. (1st December 2020) - Guo, Zhaodong; Liu, Jin; Sun, Guoli; Song, Feier; Lei, Li; He, Yibo; Liu, Bowen; Chen, Shiqun; Liu, Yong; Chen, Jiyan
Abstract: Background: This study aimed to clarify the association of post-percutaneous coronary intervention (PCI) acute heart failure (AHF) with all-cause long-term mortality in patients with chronic kidney disease (CKD). Methods: In this prospective, observational study, 610 patients with CKD and coronary artery disease (CAD) undergoing PCI were included in the final analysis. Patients were divided to the non post-PCI AHF group ( n  = 557) and the post-PCI AHF group ( n  = 53). The diagnosis of post-PCI AHF was based on symptoms, prior cardiovascular history, and potential cardiac and noncardiac precipitants. Results: The overall incidence of post-PCI AHF was 53/610 (8.7%). The incidence of all-cause long-term mortality was significantly higher in the post-PCI AHF group than in the non post-PCI AHF group (50.9% vs 23.2%, P  < .01). The median follow-up period was 7.3 years (interquartile range: 3.7–8.4). After adjusting for left ventricular ejection fraction <40% at discharge, CKD stage, acute myocardial infarction, age and smoking, post-PCI AHF was the strongest predictor of all-cause long-term mortality (hazard ratio: 8.08; 95% CI: 3.04–21.48; P  < .01). Conclusions: In patients with CKD and CAD undergoing PCI, post-PCI AHF is the strongest predictor of all-cause long-term mortality. Highlights: Relevant studies about the association of post-PCI AHF with long-term mortality are scarce. In patients with CKD and CAD, post-PCI AHF is the strongest predictor of long-term mortality. Type 4 CRS may be one of the potential risk factors for post-PCI AHF.